Trabecular metal acetabular components reduce the risk of revision following primary total hip arthroplasty: A propensity score matched study from the National Joint Registry for England and Wales - Matharu, G; Judge, A; Murray, D; Pandit, H (Elsevier, 2017)
Background Trabecular metal (TM) coated acetabular components are increasingly used in both primary and revision total hip arthroplasty (THA). However, previous studies assessing TM acetabular components have been small single-centre cohorts with most lacking a control group. We compared revision rates following primary THA between TM and non-TM coated acetabular components. Methods A retrospective observational study was performed using National Joint Registry data, which included primary THAs with the same cementless acetabular component (either TM or non- TM coated). TM and non-TM implants were matched for multiple potential confounding factors using propensity scores. Outcomes following primary THA (revision for all-cause acetabular indications, aseptic acetabular loosening, and infection) were compared between matched groups using competing risk regression analysis. Results In 18,200 primary THAs (9,100 TM and 9,100 non-TM), the overall prevalence of acetabular revision, revision for aseptic acetabular loosening, and septic revision was 1.2%, 0.13%, and 0.59% respectively. Five-year revision rates for all-causes (1.0% vs. 1.8%; sub-hazard ratio (SHR)=0.57, 95% CI=0.43-0.76; p<0.001), aseptic acetabular loosening (0.1% vs. 0.2%; SHR=0.35, CI=0.14-0.90; p=0.029), and infection (0.5% vs. 0.9%; SHR=0.51, CI=0.34-0.76; p=0.001) were all lower in TM compared with non-TM implants. Conclusion Following primary THA, TM coated implants had a reduced risk of both aseptic and septic revision compared with non-TM implants. Although absolute differences in revision risk were small, they may be clinically significant if TM designs were implanted in more complex cases.